Macro- and meso-level contextual influences on health care inequities among American Indian elders - Cathleen E. Willging; Elise Trott Jaramillo; Emily Haozous; David H. Sommerfeld; Steven P. Verney (BMC, 2021)
Abstract Background American Indian elders, aged 55 years and older, represent a neglected segment of the United States (U.S.) health care system. This group is more likely to be uninsured and to suffer from greater morbidities, poorer health outcomes and quality of life, and lower life expectancies compared to all other aging populations in the country. Despite the U.S. government's federal trust responsibility to meet American Indians' health-related needs through the Indian Health Service (IHS), elders are negatively affected by provider shortages, limited availability of health care services, and gaps in insurance. This qualitative study examines the perspectives of professional stakeholders involved in planning, delivery of, and advocating for services for this population to identify and analyze macro- and meso-level factors affecting access to and use of health care and insurance among American Indian elders at the micro level. Methods Between June 2016 and March 2017, we undertook in-depth qualitative interviews with 47 professional stakeholders in two states in the Southwest U.S., including health care providers, outreach workers, public-sector administrators, and tribal leaders. The interviews focused on perceptions of both policy- and practice-related factors that bear upon health care inequities impacting elders. We analyzed iteratively the interview transcripts, using both open and focused coding techniques, followed by a critical review of the findings by a Community Action Board comprising American Indian elders. Results Findings illuminated complex and multilevel contextual influences on health care inequities for elders, centering on (1) gaps in elder-oriented services; (2) benefits and limits of the Affordable Care Act (ACA); (2) invisibility of elders in national, state, and tribal policymaking; and (4) perceived threats to the IHS system and the federal trust responsibility. Conclusions Findings point to recommendations to improve the prevention and treatment of illness among American Indian elders by meeting their unique health care and insurance needs. Policies and practices must target meso and macro levels of contextual influence. Although Medicaid expansion under the ACA enables providers of essential services to elders, including the IHS, to enhance care through increased reimbursements, future policy efforts must improve upon this funding situation and fulfill the federal trust responsibility.